Parental Consideration of Children’s Futures: Indonesian Adaptation of the Parenting-Related CFC Scale - Anwar, Shafira Rezky; Royanto, Lucia RM (Jurnal Psikologi, 2025)
The Parenting-adapted Consideration of Future Consequences (pCFC) scale is a relatively recent instrument developed to assess time orientation in parenting decision-making. However, it had not previously been adapted for use in the Indonesian context. This study aimed to develop an Indonesian version of the pCFC and to evaluate its validity and reliability among Indonesian parents. The adaptation process followed a six-stage procedure: pre-condition, test development, confirmation, administration, scoring and interpretation, and documentation. Data from 197 parents of children aged 3–6 years were analysed using item factor analysis (IFA) to examine internal structure and McDonald’s omega to estimate internal consistency. Results supported the original two-factor model, distinguishing between future-oriented and immediate-oriented perspectives. After removing one low-performing item, the final Indonesian version comprised 13 items with significant factor loadings and acceptable model fit. Reliability estimates indicated satisfactory internal consistency for both the future-oriented factor and the total scale score. However, the immediate-oriented factor demonstrated lower reliability, warranting cautious interpretation of its scores. Overall, these findings provide preliminary support for the use of the Indonesian pCFC scale in assessing how parents weigh short- and long-term consequences in their parenting decisions. Recommendations for enhancing the psychometric quality of the immediate-oriented factor are also discussed.